Socio-Cultural Dominance in School-Choice Intentions: The Moderating Role of Environmental Conditions in a PLS-SEM Model - Hidayati, Abna; Ardi, Zadrian; Putra, Ade Herdian; Rahmi, Ulfia; Pratiwi, Rahmi; Masriani, Elsa; Arina, Novra; Hafanos, Robby; Ramadona, Dasatry Dwi (International Journal of Research in Counseling and Education, 2025)
Parents’ Ability to Choose School reflects a complex decision-making process that goes beyond administrative considerations and involves social, cultural, economic, and environmental factors. This study aims to examine the effects of socio-cultural factors, economic conditions, and environmental conditions on parents’ Ability to School Choose, as well as to test the moderating role of socio-cultural factors. A quantitative explanatory design was employed with data collected from parents in Payakumbuh City, West Sumatra, using an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that sociocultural factors and environmental conditions have significant effects on parents’ ability to choose a school, while economic factors do not show a significant direct effect. Furthermore, sociocultural factors significantly moderate the relationship between environmental conditions and the ability to choose a school but do not moderate the relationship between economic factors and the ability to choose a school. These findings highlight the dominant role of the sociocultural context in shaping school choice decisions and underscore the importance of culturally sensitive educational policies.